2014
DOI: 10.1111/jsm.12645
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Bother in Men with Advanced Prostate Cancer Undergoing Androgen Deprivation Therapy

Abstract: The majority of APC patients undergoing ADT will experience sexual dysfunction, but there is variability in their degree of sexual bother. Psychosocial aspects of sexual functioning should be considered when evaluating men's adjustment to ADT effects. Assessment of sexual bother may help identify men at risk for more general distress and lowered QOL. Psychosocial interventions targeting sexual bother may complement medical treatments for sexual dysfunction and be clinically relevant, particularly for younger m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
2
31
0
2
Order By: Relevance
“…These findings echo those of Benedict et al . who found that higher levels of sexual bother was related to greater relationship cohesion and satisfaction in ADT patients . However, when testing the direct relationship between sexual bother and dyadic adjustment, contrary to Benedict et al ., the results of this study showed that both negative mood and higher levels of sexual bother were related to worse relationship outcomes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These findings echo those of Benedict et al . who found that higher levels of sexual bother was related to greater relationship cohesion and satisfaction in ADT patients . However, when testing the direct relationship between sexual bother and dyadic adjustment, contrary to Benedict et al ., the results of this study showed that both negative mood and higher levels of sexual bother were related to worse relationship outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…Sexual bother in PCa patients on ADT has also been shown to be related to both relationship adjustment and depression . These studies all point to the likelihood that patients on ADT would have more difficulties in their relationships than patients not on ADT.…”
Section: Introductionmentioning
confidence: 83%
“…Cultural issues related to privacy preservation may justify our sexual function scores. Indeed, PC patients often experience distressing sexual effects resulting in a range of sexual problem-however most patients did not report any sexual bother [31] [32].…”
Section: Hrqol Prospective Evolution Analysis Along Five Years Since mentioning
confidence: 99%
“…It includes incontinence, increased urinary frequency or urgency, pain upon urination, obstruction or irritating voiding symptoms. These clinical manifestations are common in PC patients and the impact of these symptoms in HRQoL depends on their baseline levels and clinical support [31] [32].…”
Section: Hrqol Prospective Evolution Analysis Along Five Years Since mentioning
confidence: 99%
See 1 more Smart Citation